Diverse Particle Carriers Prepared by Co‐Precipitation and Phase Separation: Formation and Applications. Issue 1 (7th September 2020) - Sun, Zhu; Wu, Baiheng; Ren, Yixin; Wang, Zhongzhen; Zhao, Chun‐Xia; Hai, Mingtan; Weitz, David A.; Chen, Dong
Abstract: Nanoparticles with diverse structures and unique properties have attracted increasing attention for their widespread applications. Co‐precipitation under rapid mixing is an effective method to obtained biocompatible nanoparticles and diverse particle carriers are achieved by controlled phase separation via interfacial tensions. In this Minireview, we summarize the underlying mechanism of co‐precipitation and show that rapid mixing is important to ensure co‐precipitation. In the binary polymer system, the particles can form four different morphologies, including occluded particle, core‐shell capsule, dimer particle, and heteroaggregate, and we demonstrate that the final morphology could be controlled by surface tensions through surfactant, polymer composition, molecular weight, and temperature. The applications of occluded particles, core‐shell capsules and dimer particles prepared by co‐precipitation or microfluidics upon the regulation of interfacial tensions are discussed in detail, and show great potential in the areas of functional materials, colloidal surfactants, drug delivery, nanomedicine, bio‐imaging, displays, and cargo encapsulation. Abstract : Mixing matters : Co‐precipitation under rapid mixing and controlled phase separation by tuning the interfacial tensions are versatile method to prepare occluded particles, core‐shell capsules, dimer particles and heteroaggregates. This Minireview outlines the formation and applications of these particles, which provide countless interesting possibilities in functional materials, colloidal surfactants, imaging, cargo encapsulation and drug delivery.